Hubungan Kecerdasan Emosional Dengan PengelolaanKelas Elektis Pada Guru Tk Di Kecamatan Polokarto Kabupaten Sukoharjo Tahun 2015/2016 - DINIANTI, NONI AZZARI; , Drs. Ilham Sunaryo, M.Pd AUD (2016)
Teacher represent tip of lance efficacy of development of nation and considered to be key figure determining efficacy in reaching target and function education of national representing mirroring of education quality. That is why learn to be claimed to have productive performance. Emotional intellegence of teacher represent ability of teacher in comprehending, recognizing, improving, managing and leading self-motivation alone and educative participant to be is optimal is target of study which will reach. Goods have of course there is many matter able to influence teacher performance. As for target of which will reach in this research is to know there is do not it him relation among emotional intellegence of teacher of kindergarten with management of class of elektis in District Of Polokarto Sukoharjo year 2015 / 2016. Research type the used is quantitative descriptive research. Big of taken by sampel is entirety 70 teacher with Proportional Random Sampling. Technique data collecting use enquette. Examination of hypothesis use correlation analysis of product moment. Pursuant to result of researcher data analisi in examination of hypothesis able to know that value of r pearson of correlation equal to - 461 with signifikansi equal to 0,000>0,05 ( p = 0,000; p<0,05) Hence can be pulled by conclusion that there are [relation/link] [among/between] emotional intellegence with management of class of elektis at teacher of kindergarten in District Of Polokarto Sukoharjo Year 2015 / 2016.